Service Quality Expectation And Perception Towards Universiti Utara Malaysia - Mohd. Jamil, Mohd. Noor (2002)

(untitled)
This study was based on the SERVQUAL Model of Parasuraman, Zeithaml and Berry (1985,1988). Its main intention was to evaluate the gap between the expectation and perception and also the satisfaction of UUM students towards the supportive facilities of the university. The study showed that there was dissatisfaction voiced out by students on the five dimensions of SERVQUAL (tangible, reliability, responsiveness, assurance and empathy) of the university. There is also dissatisfaction towards some of the supportive facilities of the university (Pasaraya at UUM's Mall, the internal UUM bus services, the public telephone and the local buses). The results of the assessment played a crucial role as a reflection for the university. From the findings, university could make some paradigm changes of its weak five entities (tangible, reliability, responsiveness, assurance and empathy) towards the achievement of customers' greatest satisfaction. Satisfaction of the university's service quality will enhance the university's image and will raise this university as their first choice to study. The study showed that the attainment of ISO 9002 1994 by any organization does not mean or reflect that the customer would acquire satisfaction towards the five dimension of the SERVQUAL.